Experience with aortic arch inclusion technique using artificial blood vessel for type A aortic dissection: an application study - Qingfeng Li; Bin Li; Shuqiang Xi; Zhaobin Li; Zhe Zhu; Zeyue Jin; Fan Yang; Lei Liu (Journal of Cardiothoracic Surgery, 2024)
Abstract Background This study aimed to elucidate the methodology and assess the efficacy of the aortic arch inclusion technique using an artificial blood vessel in managing acute type A aortic dissection (ATAAD). Methods We conducted a retrospective review of 18 patients (11 males and 7 females, average age: 56.2 ± 8.6 years) diagnosed with ATAAD who underwent total aortic arch replacement (TAAR) using an artificial vascular “inclusion” between June 2020 and October 2022. During the operation, deep hypothermic circulatory arrest (DHCA) and selective antegrade cerebral perfusion (ACP) of the right axillary artery were employed for brain protection. The ‘inclusion’ total aortic arch replacement and stented elephant trunk (SET) surgery were performed. Results Four patients underwent the Bentall procedure during the study, with one additional patient requiring coronary artery bypass grafting (CABG) due to significant involvement of the right coronary orifice. Three patients died during postoperative hospitalization. Other notable complications included two cases of postoperative renal failure necessitating continuous renal replacement therapy (CRRT), one case of postoperative double lower limb paraplegia, and one case of cerebral infarction resulting in unilateral impairment of the left upper limb. Eleven patients underwent computed tomography angiography (CTA) examinations of the aorta three months to one-year post-operation. The CTA results revealed thrombosis in the false lumen surrounding the aortic arch stent in seven patients and complete thrombosis of the false lumen around the descending aortic stent in eight patients. One patient had partial thrombosis of the false lumen around the descending aortic stent, and another patient’s false lumen in the thoracic and abdominal aorta completely resolved after one year of follow-up. Conclusions Incorporating vascular graft in aortic arch replacement simplifies the procedure and yields promising short-term outcomes. It achieves the aim of total arch replacement using a four-branch prosthetic graft. However, extensive sampling and thorough, prolonged follow-up observations are essential to fully evaluate the long-term results.